General revealed preference theory - Christopher P. Chambers; Federico Echenique; Eran Shmaya (Theoretical Economics, 2017)
We generalize the standard revealed preference exercise in economics, and prove a sufficient condition under which the revealed preference formulation of an economic theory has universal implications and when these implications can be recursively enumerated. We apply our theorem to two theories of group behavior: the theory of group preference and the theory of Nash equilibrium.
Keywords: D0; 330; Revealed-preference theory